2014
DOI: 10.1088/0004-637x/785/2/148
|View full text |Cite
|
Sign up to set email alerts
|

ATMOSPHERIC CHARACTERIZATION OF FIVE HOT JUPITERS WITH THE WIDE FIELD CAMERA 3 ON THEHUBBLE SPACE TELESCOPE

Abstract: We probe the structure and composition of the atmospheres of 5 hot Jupiter exoplanets using the Hubble Space Telescope Wide Field Camera 3 (WFC3) instrument. We use the G141 grism (1.1-1.7 µm) to study and CoRoT-1b in transit, TrES-3b in secondary eclipse, and WASP-4b in both. This wavelength region includes a predicted absorption feature from water at 1.4 µm, which we expect to be nondegenerate with the other molecules that are likely to be abundant for hydrocarbon-poor (e.g. solar composition) hot Jupiter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 62 publications
(94 reference statements)
5
65
2
Order By: Relevance
“…Follow-up transit observations have confirmed and refined the planetary parameters of this system Colón et al 2010;Croll et al 2010;Gilliland et al 2010;Mislis et al 2010;O'Donovan et al 2010;Scuderi et al 2010;Southworth 2011;Kipping & Bakos 2011;Kipping & Spiegel 2011;Christiansen et al 2011;Barclay et al 2012;Schröter, Schmitt & Müller 2012;Esteves et al 2013;Ranjan et al 2014). In addition, Rossiter-McLaughlin effect measurements of the system found that TrES-2b is aligned with its host star's equator (−9 • ± 12 • ) and orbits in a prograde orbit (Winn et al 2008a).…”
Section: Tres-2bmentioning
confidence: 72%
See 2 more Smart Citations
“…Follow-up transit observations have confirmed and refined the planetary parameters of this system Colón et al 2010;Croll et al 2010;Gilliland et al 2010;Mislis et al 2010;O'Donovan et al 2010;Scuderi et al 2010;Southworth 2011;Kipping & Bakos 2011;Kipping & Spiegel 2011;Christiansen et al 2011;Barclay et al 2012;Schröter, Schmitt & Müller 2012;Esteves et al 2013;Ranjan et al 2014). In addition, Rossiter-McLaughlin effect measurements of the system found that TrES-2b is aligned with its host star's equator (−9 • ± 12 • ) and orbits in a prograde orbit (Winn et al 2008a).…”
Section: Tres-2bmentioning
confidence: 72%
“…Several follow-up primary transit photometry studies of the system find no signs of a changing period (Bean 2009;Gillon et al 2009;Csizmadia et al 2010;Rauer et al 2010;Southworth 2011;Sada et al 2012;Ranjan et al 2014). CoRoT-1b's atmosphere may have a temperature inversion (Alonso et al 2009;Gillon et al 2009;Rogers et al 2009;Snellen, de Mooij & Albrecht 2009;Zhao et al 2012) or an isothermal profile (Deming et al 2011).…”
Section: Corot-1bmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the currently available ground-based data for this A10, page 14 of 23 (2015), Turner et al (2016). Black squares denote the HST WFC3 data by Ranjan et al (2014). Synthetic spectra for the homogeneously cloudy models with X max = 3 × 10 −4 Z Pl are shown as teal and red solid lines for the DHS and Mie opacity, respectively.…”
Section: Tres-4bmentioning
confidence: 99%
“…Measurements of the Rossiter-McLaughlin effect (Narita et al 2010, N10 hereafter) revealed close spin-orbit alignment of the TrES-4 system. Atmospheric characterization measurements have been obtained by Knutson et al (2009), who detected a temperature inversion in the TrES-4b broadband infrared emission spectrum with Spitzer/IRAC during secondary eclipse, and by Ranjan et al (2014), who presented a featureless transmission spectrum of TrES-4b using HST/WFC3 during primary transit. Constraints from the secondary eclipse measurements and A&A 575, L15 (2015) expanded radial-velocity (RV) datasets , K14 thereafter) indicate a probable circular orbit for TrES-4b.…”
Section: Introductionmentioning
confidence: 99%